2019
DOI: 10.1515/cclm-2018-1109
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of stability profiles of common chemistry analytes in serum stored at six graded temperatures

Abstract: Background Many reports address the stability of biochemical analytes in serum. However, studies covering a wide range of storage temperatures are unavailable. Using equipment enabling precise temperature control, we investigated the effect of six different storage temperatures on serum analytes. Methods Serum specimens from seven healthy volunteers were obtained and divided into multiple aliquots for storage at −30, −20, −10, 0, 4, and 25 °C. On days 1, 3, 7, 14, 28 and 56, the aliquots stored at each temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
3
11
0
4
Order By: Relevance
“…Demeester et al reported similar results after a 7-day storage period in BD Barricor plasma tubes for albumin, ALP, AST, glucose, LD, Na and K ( 17 ). Shimizu et al obtained results comparable to ours for AST and LDH in serum samples after storing samples for 7 days on 4 °C ( 20 ).…”
Section: Discussionsupporting
confidence: 83%
“…Demeester et al reported similar results after a 7-day storage period in BD Barricor plasma tubes for albumin, ALP, AST, glucose, LD, Na and K ( 17 ). Shimizu et al obtained results comparable to ours for AST and LDH in serum samples after storing samples for 7 days on 4 °C ( 20 ).…”
Section: Discussionsupporting
confidence: 83%
“…The results of our study are consistent with the ones obtained by Shimizu Y, An B and Heins M [3][4][5], who reported that activity decreases in refrigerated samples, whereas it remains stable at RT. In contrast, Oddoze C [6] observed an increased activity.…”
supporting
confidence: 93%
“…De acuerdo con nuestros resultados, se observa una influencia muy importante de la temperatura en la estabilidad, siendo ésta cinco veces inferior a temperatura ambiente que en muestras refrigeradas. La mayor pérdida de estabilidad a temperatura ambiente concuerda con lo observado de manera general [22,23] Hasta donde sabemos, este es el primer estudio que evalúa la influencia de variables no habituales en la estabilidad de la ALT, como son la concentración catalítica inicial, la plataforma analítica y el modelo experimental [7,9,11].…”
Section: Discussionunclassified
“…Lo contrario pasaría con los individuos con concentración catalítica de ALT muy estable en el tiempo, para los cuales se podrían conservar las muestras durante periodos superiores. Este efecto podría en parte deberse a la presencia de isoenzimas termosensibles, como se sugiere por ejemplo para la lactato deshidrogenasa [23].…”
Section: Discussionunclassified